2003
DOI: 10.1097/00002093-200301000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Brain Correlates of Performance in a Free/Cued Recall Task With Semantic Encoding in Alzheimer Disease

Abstract: Summary:The goal of this study was to explore in patients with Alzheimer's disease (AD) the brain correlates of free and cued recall performance using an adaptation of the procedure developed by Grober and Buschke (1987). This procedure, which ensures semantic processing and coordinates encoding and retrieval, has been shown to be very sensitive to an early diagnosis of AD. Statistical parametric mapping (SPM 99) was used to establish clinicometabolic correlations between performance at free and cued verbal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
1
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 74 publications
7
34
1
8
Order By: Relevance
“…A similar result has been reported by Lekeu et al in AD patients [17] and has been recently reported by Philippi et al in patients with mild cognitive impairment using the Word version of the FCSRT [20]. It has been suggested that this association is related to the implication of search activity and strategic retrieval of the information during free recall [20].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A similar result has been reported by Lekeu et al in AD patients [17] and has been recently reported by Philippi et al in patients with mild cognitive impairment using the Word version of the FCSRT [20]. It has been suggested that this association is related to the implication of search activity and strategic retrieval of the information during free recall [20].…”
Section: Discussionsupporting
confidence: 87%
“…This interference task was followed by a free recall trial for all 16 items, and a cued recall trial for those items not retrieved at free recall, and for which the same semantic cues as those used during encoding were verbally given. The first and second recall trials were followed by 20 seconds of counting backwards [17]. Overall, both versions of the FCSRT yield several memory measurements, namely the immediate recall (IR) (for the study phase), free recall (FR), cued recall, total recall (TR) scores (maximum score = 48) and sensitivity to cueing index (for the memory phase).…”
Section: Episodic Memory Testing: Word and Picture Fcsrt Versionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the second interpretation, a number of neuropathological, neuropsychological, and neuroimaging studies have suggested that AD can be characterized as a disconnection syndrome (Azari et al, 1992;Leuchter et al, 1992;Morris, 1994;Collette et al, 2002;Lekeu et al, 2003a). Thus, loss of synaptic contacts in associative cortices and limbic structures would interrupt long connecting pathways in AD (Hyman et al, 1984;Pearson et al, 1985).…”
Section: Neural Substrate Of Controlled Processesmentioning
confidence: 90%
“…Notably, decreased efficiency in the frontal regions was mainly located in the right hemisphere. Previous studies have shown that the decreased activity of right prefrontal regions are associated with the worse memory performance in AD patients (Grady et al, 2001;Lekeu et al, 2003), implying that the structural decline in the right hemisphere likely links with the memory loss. Together, our results suggest that the WM degenerated alterations in these frontal regions might influence information transmission and functional integration for AD patients.…”
Section: Regional Characteristics In Anatomical Brain Network In Admentioning
confidence: 95%